Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Kerja, dan Disiplin Kerja terhadap Kinerja Guru pada Sekolah Menengah Kejuruan SMK Negeri 1 Musuk Boyolali - Siti Musarofah; Listyowati Puji Rahayu; Luki Sri Anggoro Wati (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Teacher performance is one of the key factors in determining the quality of education and the achievement of school objectives. Several factors that are assumed to influence teacher performance include transformational leadership style, work motivation, and work discipline. This study aims to analyze the effect of transformational leadership style, work motivation, and work discipline on teacher performance at SMK Negeri 1 Musuk Boyolali. The research employed a quantitative method with descriptive and verificative approaches. The population consisted of 50 teachers, and all members of the population were selected as respondents using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 25. The results revealed that work motivation had a positive and significant effect on teacher performance. In contrast, transformational leadership style and work discipline did not have a significant partial effect on teacher performance. However, simultaneously, transformational leadership style, work motivation, and work discipline significantly affected teacher performance. The Adjusted R Square value of 0.324 indicates that these three variables explain 32.4% of the variation in teacher performance, while the remaining 67.6% is influenced by other factors outside the scope of this study. The findings imply that enhancing work motivation should be prioritized in efforts to improve teacher performance, while leadership and work discipline should continue to be strengthened to support a more effective working environment.